Validation of the NULL‐EASE Score for Predicting Survival in a Multiethnic Asian Cohort of Out‐of‐Hospital Cardiac Arrest - Shir Lynn Lim; Siew Pang Chan; Nur Shahidah; Kai Lee Woo; Sean Shao Wei Lam; Benjamin Sieu‐Hon Leong; Gregory Y. H. Lip; Marcus Eng Hock Ong (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background NULL‐PLEASE is a simple and accurate clinical scoring system developed in a Western cohort of patients with out‐of‐hospital cardiac arrest (OHCA). The need for blood test results limits its use in early stages of care. We adapted and validated the NULL‐EASE score (without laboratory tests) in an independent, multiethnic Asian cohort of patients with out‐of‐hospital cardiac arrest. Methods and Results Using the Singapore OHCA registry, we included consecutive adult patients with out‐of‐hospital cardiac arrest who survived to hospital admission between April 2010 to December 2020. In‐hospital mortality was the primary outcome. Logistic regression analyses were performed with STATA MP v18. Of 3274 patients (median age 64, interquartile range 54–75; 67.9% male) included in the study, 2476 (75.6%) had in‐hospital mortality. NULL‐EASE score was significantly lower in survivors compared with nonsurvivors (median [inter quartile range] 3 [1–4] versus 6 [4–7]; P<0.001) and strongly predictive of mortality (area under receiver operating characteristic, 0.81 [95% CI, 0.79–0.83]). Patients with a score of ≥3 had higher odds of mortality (adjusted odds ratio, 8.11 [95% CI, 6.57–10.00]) when compared with those with lower scores, after adjusting for sex, residential arrest, diabetes, respiratory disease, and stroke. A cutoff value of ≥3 predicted mortality with 92.2% sensitivity, 84.1% positive predictive value, 46.1% specificity, and 65.5% negative predictive value. NULL‐EASE score performed better in younger compared with older patients (area under receiver operating characteristic, 0.82 versus 0.77, P=0.008). Conclusions The NULL‐EASE score has good discriminative performance (sensitivity and accuracy) in our multiethnic Asian cohort, but the cutoff of ≥3 falls short of the desired level of specificity for therapeutic decision‐making.